2011
DOI: 10.1155/2011/698975
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Utility of Alpha Fetoprotein and HCCR-1, Alone or in Combination, in Patients with Chronic Hepatitis, Liver Cirrhosis and Hepatocellular Carcinoma

Abstract: Serum alpha fetoprotein (AFP) is the most widely used tumor marker in detecting patients with hepatocellular carcinoma (HCC). However, it has been indicated that HCCR-1 (human cervical cancer oncogene 1) might be supplementary to AFP in the detection. We conducted a prospective study in 120 normal and 524 liver disease patients to evaluate the significance of simultaneous measurement of 2 tumor markers (AFP and HCCR-1) in the diagnosis of HCC through the cohort study in Korea and China. We also performed immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 27 publications
(51 reference statements)
0
9
0
Order By: Relevance
“…Serum HCCR was positive in 76.9% (40 of 52) ANHC patients ( 147 ); in addition, nine patients with metastatic lesions who were negative for AFP were positive for HCCR. However, another study showed that HCCR-1 has a positive rate of only 48.5% (63 of 130) in ANHC ( 148 ). In a multicenter prospective study ( 5 ), HCCR-1 levels did not significantly correlate with HCC clinicopathological characteristics such as age, gender, tumor size, and lymph node metastasis, but positively correlated with histological grading.…”
Section: Blood Biomarkers For Anhc Diagnosismentioning
confidence: 98%
“…Serum HCCR was positive in 76.9% (40 of 52) ANHC patients ( 147 ); in addition, nine patients with metastatic lesions who were negative for AFP were positive for HCCR. However, another study showed that HCCR-1 has a positive rate of only 48.5% (63 of 130) in ANHC ( 148 ). In a multicenter prospective study ( 5 ), HCCR-1 levels did not significantly correlate with HCC clinicopathological characteristics such as age, gender, tumor size, and lymph node metastasis, but positively correlated with histological grading.…”
Section: Blood Biomarkers For Anhc Diagnosismentioning
confidence: 98%
“…Several studies indicate that HCCR expression increases as liver cells gradually progress from LC to HCC [ 5 ]; thus, HCCR expression may be a useful marker for HCC progression and/or prognosis [ 3 ]. We have made similar observations in clinical samples.…”
Section: Discussionmentioning
confidence: 99%
“…HCC is now the most common cancer in rural areas of China and the second most common in urban areas [ 2 ]. Recent research has supported that human cervical cancer proto-oncogene (HCCR) is a specific and sensitive biomarker independent of serum alpha-fetoprotein (AFP) for the diagnosis of HCC [ 3 5 ]. Several studies report that normal liver tissues show minimal, or no, HCCR expression, whereas expression is much higher in individuals with chronic hepatitis, liver cirrhosis (LC), or small and large HCC [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Their combined use appears to increase the accuracy and sensitivity of serological diagnosis of HCC (24)(25)(26)(27)(28)(29)(30). AFP-L3% and DCP are HCC markers that can be measured on the same platform, making testing more friendly to clinical laboratories.…”
Section: Discussionmentioning
confidence: 99%